Complex evolutionary history of two ecologically significant grass genera, Themeda and Heteropogon (Poaceae: Panicoideae: Andropogoneae). (9th March 2021) - Arthan, Watchara; Dunning, Luke T; Besnard, Guillaume; Manzi, Sophie; Kellogg, Elizabeth A; Hackel, Jan; Lehmann, Caroline E R; Mitchley, Jonathan; Vorontsova, Maria S
Abstract: Themeda and Heteropogon are closely related grass genera frequently dominant in tropical C4 grasslands. Relationships between them are poorly resolved, impeding ecological study, especially of T. triandra with a broad distribution from Africa to East Asia, and H. contortus with a pantropical distribution. Our analyses of plastome and nuclear genomes with comprehensive sampling of Themeda and Heteropogon demonstrate that neither genus is monophyletic as currently circumscribed. Plastome and nuclear data place H. melanocarpus and H. ritchiei in Themeda . Nested in T. triandra are T. quadrivalvis and T. unica, demonstrating that this widespread species is more morphologically diverse than previously recognized. Heteropogon fischerianus is nested in H. contortus . The picture is more complex for H. triticeus that is sister to H. contortus in the nuclear analysis and to Cymbopogon in the plastome analysis. This incongruence between nuclear and plastid phylogenetic trees suggests hybridization between Cymbopogon -related genome donors and H. contortus . Plastome dating estimates the Themeda–Heteropogon crown age at c. 7.6 Myr, consistent with the Miocene C4 grassland expansion. Themeda triandra and H. contortus diversified 1–2 Mya in the Pleistocene. These results establish a foundation for studying the history of these ecologically significant widespread grasses and the ecosystems they form.